Pelatihan Memanfaatkan Lahan Sempit untuk Budidaya Sayuran Organik - Aman Suyadi; Bambang Nugroho (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
IbM program aimed at improving capability and skill of cadres and PKK members of RW 12 and 13 Karangklesem village in optimalizing narrow-land area in their neighbourhood through improving capability and skill on verticulture technology mastery on organic vegetables from the making of organic fertilizer, biological pesticide, seed seedling, planting media, planting, plant treatment, harvesting and post harvesting, and capability of vegetables (agribusiness) entrepreneurship. The next aim was to handle the household waste, to create beautiful, green, and aesthetic environment, and to earn additional income for the cadres and PKK members of RW 12 and 13 from their organic vegetable sales.The method used in this IbM program was training and direct practice, assisting, fostering, and partnership with the cadres and PKK members of RW 12 and 13 at Karangklesem village.Utilization of narrow-land area has been conducted around RW 12 and 13 at Karangklesem village by conducting the following activities: (1) Bioactivator making and liquid organic fertilizer and compost training. The results were 20 liters bioactivator, 200 liters liquid organic fertilizer, and 750 kilograms compost, (2) the technique of making biological pesticide training; the result was 200 liters of biological pesticide, (3) organic vegetable virticultur technique training; the result was 47 sets of organic vegetables in verticulture system, (4) post-harvesting technique of organic vegetables, and (5) entrepreneurship training covering the training of book keeping, business analysis of verticulture organic vegetable and marketing management.The conclusion of this IbM program was that there was an improvement on capability and skill of the cadres and PKK members of RW 12 and 13 Karangklesem village in mastering the verticulture technology of organic vegetables from the making of bioactivator, liquid organic fertilizer, compost, biological pesticide, seed seedling, planting media, planting and plant treatment, harvesting and post-harvesting treatment, and organic vegetable entrepreneurship